2020
DOI: 10.1038/s41525-020-00149-6
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian Initiative on Precision Medicine (BIPMed): fostering genomic data-sharing of underrepresented populations

Abstract: The development of precision medicine strategies requires prior knowledge of the genetic background of the target population. However, despite the availability of data from admixed Americans within large reference population databases, we cannot use these data as a surrogate for that of the Brazilian population. This lack of transferability is mainly due to differences between ancestry proportions of Brazilian and other admixed American populations. To address the issue, a coalition of research centres created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
2
29
0
4
Order By: Relevance
“…Databases that specifically focus on specific disease/gene(s) are easier to manage, through which larger genetic databases can be supported, enabling collaboration and data exchange. As a part of the Brazilian Initiative for Precision Medicine (Rocha, Secolin, Rodrigues, Carvalho, & Lopes-Cendes, 2020), the BRCA database, documenting 180 variants in BRCA1 and BRCA2 genes that have been found in the Brazilian population is a first step towards this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Databases that specifically focus on specific disease/gene(s) are easier to manage, through which larger genetic databases can be supported, enabling collaboration and data exchange. As a part of the Brazilian Initiative for Precision Medicine (Rocha, Secolin, Rodrigues, Carvalho, & Lopes-Cendes, 2020), the BRCA database, documenting 180 variants in BRCA1 and BRCA2 genes that have been found in the Brazilian population is a first step towards this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Accessing the genomic sequences of the general population is relevant to identify the genetic variability involved in the molecular mechanisms of infection 20 . Also, it is known that the admixed Brazilian population is underrepresented in large public databases 21,22 , and previous studies revealed variants present exclusively in Brazilian indivuduals 19,24 .…”
Section: Discussionmentioning
confidence: 99%
“…We studied 27 human COVID-19-related genes and the HLA region in two public genomic databases of admixed Brazilians (BIPMed, www.bipmed.org 19 ; ABraOM http://abraom.ib.usp.br/ 24 ), and additional samples from individuals born in three different towns of south-eastern Brazil. We reported the variants and HLA alleles found in these samples and compared them with worldwide populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated 257 individuals from BIPMed ( Rocha et al, 2020 ), 609 from ABraOM ( Naslavsky et al, 2017 ), and 88 additional exomes from individuals born in the following towns within southeastern Brazil: Barretos ( N = 30); Ribeirão Preto ( N = 30), located in the state of São Paulo; and Belo Horizonte ( N = 28), the capital of the state of Minas Gerais ( Supplementary Figure 1 ). Among individuals included in BIPMed, the birthplace of 193 individuals were included; thus, we were able to extract 21 individuals born in São Paulo city and 37 from Campinas to increase the power of regional comparisons.…”
Section: Methodsmentioning
confidence: 99%